PENGARUH SENAM NIFAS TERHADAP INVOLUSI UTERUS PADA IBU POST PARTUM HARI 1-3 DI RSUD KABELOTA - Wendi Muhammad Fadhli (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
The end of the process of exclusion does not mean that the mother is free from danger or complications. Various complications can be experienced by women during childbirth and if not handled properly will contribute significantly to the high maternal mortality rate (MMR) in Indonesia. The purpose of this study was to analyze the effect of puerperal exercise on the reduction of uterine involution in post partum mothers on 1-3 days at Kabelota Hospital. This type of research uses a quantitative approach using quasi experimental using one control group with two groups pre test and post test design. The number of samples is control 8 and the case is 8 people. Using consecutive sampling technique. The results of the study were analyzed using univariate and bivariate analysis. The results showed that there was a difference in the mean value of uterine involution in post partum mothers on 1-3 days who were not given post partum exercise and post partum mothers who were given postnatal exercise. The results of statistical tests 1-3 days obtained p = 0,000. This can be seen that the p value (probability) is lower than the p value = 0.05. It can be concluded that there is a significant effect of puerperal gymnastics on uterine involution in post partum mothers 1-3 days. It can be concluded that there is a significant effect of puerperal exercise on uterine involution in women post partum 1-3. Conclusion there is a significant influence of puerperal exercise on uterine involution in women post partum 1-3. Suggestions further increase knowledge about puerperal exercise so that it will then be motivated to do puerperal exercise. Keywords: postpartum exercise, uterine involution, post partum mother